525 Minimally Invasive Surgical Treatment of Benign Prostatic Hyperplasia: A Systematic Review. (12th October 2021) - Ting, A; Shanmugathas, N; Khoo, C; Dasgupta, R; El-Husseiny, T; Abboudi, H
Abstract: Introduction: Minimally invasive surgical treatments (MISTs) of benign prostatic hyperplasia (BPH) have evolved to offer men daycase care with preservation of urinary continence and sexual function. This systematic review evaluates trends in minimally invasive BPH surgery over the last decade Method: Systematic review (PRISMA) of Embase/MEDLINE databases (2010-2020). MISTs included Rezum, Urolift, Prostatic Artery Embolisation (PAE), Temporary Implantable Nitinol Device (TIND), Intraprostatic Injection, Transurethral Microwave Therapy (TUMT) and Transurethral Needle Ablation (TUNA). Primary outcome: urinary functional change (International Prostate Symptom Score (IPSS)/maximum flow (Qmax )). Secondary outcomes: sexual functional change (International Index of Erectile Function-5 (IIEF-5)), technical failures and complications. Results: 74 studies were included (total: 8, 917 patients). Primary: all interventions offered improvement in IPSS and Qmax ( intervention (no. studies): range IPSS change, range Qmax change, range months follow-up; Rezum (4): -46.7% to -62.7%, +17.6% to + 55.6%, 6-48; Urolift (11): -35.2% to -64.2%, +16.7% to + 89.6%, 1-60; PAE (36): -36.8% to -85.2%, +17.4% to + 155.2%, 3-38; TIND (2): -36.8% to -59.6%, +32.9% to + 95.9%, 12-36; Intraprostatic Injection (14): -24.3% to -62%, +8.7% to + 98.4%, 3-24; TUMT (4): -56.1% to -58.7%, +12.9% to + 60.2%, 6-60; TUNA (3): -17.6% to -63.2%, +3.9% to + 39%, 1-120). Secondary: 33 studies of all interventions bar TIND and TUMT reported IIEF-5 change; sexual function was largely preserved. Technical failures and Clavien-Dindo ≥3 complications were rare. Conclusions: MISTs for BPH are efficacious and safe. Randomised comparisons with long-term urinary and sexual follow-up are needed to guide choice; until then, patients should be carefully counselled based on individual priorities and circumstances.